FIGHTING DISINFORMATION IN A STRUCTURAL WAY: a case study of the Desinformante as an organizational model - Nichols, Bruno; Grohmann, Rafael (Brazilian journalism research, 2025)
ABSTRACT – This article presents a case study of Desinformante, a Brazilian project founded in 2022 as an organizational innovation in the fight against disinformation. Rather than restricting itself to a fact-checking agency model, Desinformante is a mix of media outlet – with a focus on covering disinformation in a structural and global way – and a center of articulation and coalition with various sectors, such as social movements and the judiciary. Although this dual role is common in the country’s independent media, it had not been tested in initiatives focused on combating disinformation. Based on interviews with six Desinformante workers in 2023, the article presents the potential and limits of this Brazilian experience as an organizational model for combating disinformation, as evaluated by the people who work on this initiative. It discusses the following dimensions: a) organization and internal governance; b) work routines; c) editorial policies; d) coalition initiatives. The research shows that Desinformante is a prefigurative project for combating disinformation and can inspire other organizational forms in a Majority World context. RESUMO – Este artigo apresenta um estudo de caso do Desinformante, projeto brasileiro fundado em 2022 como uma inovação organizacional no combate à desinformação. Em vez de se restringir a um modelo de agência de verificação de fatos, o Desinformante é um misto de veículo midiático – com foco na cobertura da desinformação de forma estrutural e global – e um centro de articulação e coalizão com diversos setores, como os movimentos sociais e o poder judicial. Embora este duplo papel seja comum nos meios de comunicação independentes do país, isto não tinha sido testado em iniciativas focadas no combate à desinformação. Construído a partir de entrevistas com seis trabalhadores do Desinformante em 2023, o artigo apresenta as potencialidades e limites desta experiência brasileira como modelo organizacional para o combate à desinformação sob avaliação de pessoas que trabalham nesta iniciativa. Discute as seguintes dimensões: a) organização e governança interna; b) rotinas de trabalho; c) políticas editoriais; d) iniciativas de coalizão. A pesquisa demonstra que o Desinformante é um projeto prefigurativo de combate à desinformação e pode inspirar outras formas organizacionais em um contexto de Mundo Majoritário. RESUMEN – Este artículo presenta un estudio de caso de Desinformante, un proyecto brasileño fundado en 2022 como innovación organizativa en la lucha contra la desinformación. En lugar de limitarse a un modelo de agencia de verificación de hechos, Desinformante es una mezcla de medio de comunicación – con un enfoque en la cobertura de la desinformación de manera estructural y global – y un centro de articulación y coalición con diversos sectores, como los movimientos sociales y el poder judicial. Aunque este doble papel es habitual en los medios independientes del país, no se había puesto a prueba en iniciativas centradas en la lucha contra la desinformación. A partir de entrevistas con seis trabajadores de Desinformante en 2023, el artículo presenta el potencial y los límites de esta experiencia brasileña como modelo organizativo de lucha contra la desinformación, según la evaluación de las personas que trabajan en esta iniciativa. Analiza las siguientes dimensiones: a) organización y gobernanza interna; b) rutinas de trabajo; c) políticas editoriales; d) iniciativas de coalición. La investigación demuestra que Desinformante es un proyecto prefigurativo de lucha contra la desinformación y puede inspirar otras formas organizativas en un contexto de Mundo Mayoritario.